Contribution of Geographic Learning in Growing Intelligence of Spiritual Students - Amin; Hermanto (International Journal of Science and Society, 2022)
This study attempts to identify two questions: first, what role does geography learning play in fostering students' spiritual intelligence; and second, how do socio-cultural, psychological, and demographic factors influence students' spiritual intelligence? A sample of 79 students from Teratai Putih Global Bekasi High School participated in this survey. Through the use of questionnaires, data collection techniques were implemented, and SPSS software was utilized for data analysis. The data analysis includes a test of validity using the approach of corrected item-total correlation, a test of reliability, an Independent T test, and structural equation modeling (SEM). There were no significant changes in students' spiritual intelligence depending on gender, level or class, or the type of work their parents conducted. However, there were substantial variances in students' spiritual intelligence.